The skills debate in the context of a pandemic: Are students prepared for the workplace? - Ruth Puhr (Forum Neue Medien in der Lehre Austria, 2021)
This paper explores the preparation of hospitality management students for the workplace in the context of a global health crisis. In an intrinsic mixed methods case study, student perspectives are used to problematize and evaluate conceptualizations and terminologies. The study recommends that employability, a dualistic and politicised term, be replaced by the intrinsic construct of work readiness and finds that competencies, work integrated learning and perceived relevance of the degree play instrumental roles in delivering work readiness. Context-specific and regularly updated competency frameworks are recommended. Capability emerges as a powerful and often overlooked construct.